SISTEM INFORMASI MANAJEMEN ASET MENGGUNAKAN METODE GARIS LURUS DAN MULTI ATTRIBUTE UTILITY THEORY (STUDI KASUS : SMAN 3 CIMAHI) - Tasya Wiendhyra; Nisa Hanum Harani; Roni Habibi; Rolly Maulana Awangga (Jurnal Teknologi, 2022)
Asset management carried out by SMA Negeri 3 Cimahi is intended to manage assets at the school to support education and teaching and learning activities at schools. Asset management has been managed by the head of the asset warehouse. The whole process is still done manually by written it out then transferred to Microsoft Excel. For borrowing still use manual forms that are not compiled according to the year and existing items. In impairment  of asset, there is no recommendation for deletion that can facilitate decision making for asset deletion. Based on these problems, it is necessary to make an information system that can handle the asset management process. This information system is used by three Users, namely the Principal, the warehouse (asset) and the facility wakasek. The method of depreciation of assets used to perform calculations in this study is a straight line. Then the method for making decisions on goods to be deleted is the Multi-Attribute Utility Theory method with 3 criteria,  condition of the goods, book value, and the remaining economic life. This information system is web-based to increase the efficiency of schools in using information technology. The calculation tests carried out using the system and manual get the same results, the straight-line method on school desk assets purchased in 2018 at a price of 4,000,000, the depreciation on this month is 358,568. And for the Multi Attribute Utility Theory method, a recommendation for removal is obtained, namely a wooden cabinet with a final value of 0.8.